2019
DOI: 10.3389/fphys.2019.01342
|View full text |Cite
|
Sign up to set email alerts
|

A Single Simulated Heliox Dive Modifies Endothelial Function in the Vascular Wall of ApoE Knockout Male Rats More Than Females

Abstract: IntroductionThe number of divers is rising every year, including an increasing number of aging persons with impaired endothelial function and concomitant atherosclerosis. While diving is an independent modulator of endothelial function, little is known about how diving affects already impaired endothelium. In this study, we questioned whether diving exposure leads to further damage of an already impaired endothelium.MethodsA total of 5 male and 5 female ApoE knockout (KO) rats were exposed to simulated diving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…In a previous study on ApoE KO rats, we observed no increase in oxidative stress in the pulmonary artery of ApoE KO rats when assessed by lipid peroxidation in plasma. Moreover, we found that Tempol, a superoxide scavenger, did not affect endothelium-dependent relaxation 34 . However, in the previous study the rats were younger (6–9 weeks old) and fed a standard diet while in the current study, ApoE KO rats were fed a Western diet and developed significant hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In a previous study on ApoE KO rats, we observed no increase in oxidative stress in the pulmonary artery of ApoE KO rats when assessed by lipid peroxidation in plasma. Moreover, we found that Tempol, a superoxide scavenger, did not affect endothelium-dependent relaxation 34 . However, in the previous study the rats were younger (6–9 weeks old) and fed a standard diet while in the current study, ApoE KO rats were fed a Western diet and developed significant hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 69%
“…The pulmonary artery (first bronchial artery in right lobe) and third order mesenteric were dissected and mounted in an isometric myograph (Danish Myo Technology, Aarhus, Denmark) as described previously 34 . Maximal contractile response was assessed with potassium solution (KPSS): equimolar substitution of KCl for NaCl in PSS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diving causes endothelial dysfunction in humans and experimental animals, independently of other pathology such as DCS (Brubakk et al, 2005;Lambrechts et al, 2013). We recently showed that male ApoE KO rats as young as 6-9-weeks-old have greater endothelial dysfunction in their pulmonary arteries than Sprague Dawley rats after a similar simulated dive protocol (absolute pressure of 600 kPa and decompression of 50 kPa/min), due to altered NO-dependent signaling (Berenji Ardestani et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that a single simulated dive causes endothelial dysfunction in the pulmonary arteries of male ApoE knockout rats (Berenji Ardestani et al, 2019). Endothelial dysfunction in the pulmonary arteries of ApoE KO rats was associated with altered production or bioavailability of NO and was more profound in male than in female rats (Berenji Ardestani et al, 2019).…”
Section: Introductionmentioning
confidence: 95%